Unraveling Piracy: Enforcement of Film Copyright in Indonesia's Digital Era - Seger Santoso; M. Reza Saputra; Siti Masitah; Shinta Amelia (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This study investigates the issue of film piracy in Indonesia and the efforts to enforce copyright in the digital era. The primary focus is on the case of "Mencuri Raden Saleh," which illustrates the detrimental impact of piracy on the national film industry, including financial losses and impediments to innovation. This research also evaluates the effectiveness of law enforcement measures and highlights the importance of public education and cross-sector collaboration in combating piracy. The findings provide strategic recommendations to strengthen copyright protection in Indonesia in the face of digital era challenges.